Analysis of Food & Beverage Inventory Control using Economic Order Quantity Method to Minimize Inventory Cost at Bali Taum Resort - N K I Widiastini; I P M Astawa; I G M Karma (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
Food & beverage material procurement is still being a problem at Taum Resort Bali because inventory purchases only use estimates, causing inventory costs to be quite high. The purpose of this study is to determine the control of food & beverage supplies using the economic order quantity method at Taum Resort Bali, and to find out that food & beverage supplies controlling using economic order quantity methods can minimize inventory costs at Taum Resort Bali. This research is conducted to analysis of food & beverage inventory control using economic order quantity method to minimize inventory costs at Taum Resort Bali. The results of the analysis show that inventory control using the EOQ method includes determining the amount of economic purchases, minimum inventory, maximum inventory, and reorder. The use of this EOQ method can minimize food & beverage inventory costs for food supplies including Beef Sausage by 27% Fine Chicken by 27%, Bacon Streaky LFS by 13% and overall by 23% for a year. For beverage supplies include Bali Moon 9 Vodka 700 ml by 6%, Beer Bintang Pint Small 330 ml by 21%, Coca-Cola 330 ml by 56% and overall by 33% for a year. Trough this research, it is expected that companies can carry out inventory control especially to supply food & beverage by implementing the EOQ method because the company can find out how much inventory purchases are economical, the minimum amount of inventory held, the maximum amount of inventory that can be stored in the warehouse, and reorder time so that the cost inventory can be minimized.